2016
DOI: 10.1016/j.tins.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiotics and the Manipulation of Bacteria–Gut–Brain Signals

Abstract: Psychobiotics were previously defined as live bacteria (probiotics) which, when ingested, confer mental health benefits through interactions with commensal gut bacteria. We expand this definition to encompass prebiotics, which enhance the growth of beneficial gut bacteria. We review probiotic and prebiotic effects on emotional, cognitive, systemic, and neural variables relevant to health and disease. We discuss gut–brain signalling mechanisms enabling psychobiotic effects, such as metabolite production. Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
565
0
41

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 779 publications
(668 citation statements)
references
References 156 publications
(144 reference statements)
9
565
0
41
Order By: Relevance
“…However, there is increasing evidence indicating that some cerebral functions, and particularly mood and anxiety, can be ameliorated in subjects with psychiatric conditions by the administration of probiotics 129. The word “psychobiotics” has been coined to design this specific function of probiotics 130. More studies are needed in the future to assess the effects of these preparations on cognitive functions of both healthy individuals and older patients with dementia 125,130…”
Section: Discussionmentioning
confidence: 99%
“…However, there is increasing evidence indicating that some cerebral functions, and particularly mood and anxiety, can be ameliorated in subjects with psychiatric conditions by the administration of probiotics 129. The word “psychobiotics” has been coined to design this specific function of probiotics 130. More studies are needed in the future to assess the effects of these preparations on cognitive functions of both healthy individuals and older patients with dementia 125,130…”
Section: Discussionmentioning
confidence: 99%
“…The signalling of GABA has been recorded in animals for more than 60 years (Ramesh, Tyerman, Gilliham, & Xu, ). As the major inhibitory neurotransmitter, GABA controls the neural excitation–inhibition balance of animals (Sarkar et al, ) and produces a specific effect on body metabolism and animal growth performance (Scanes, Denver, & Bowen, ). As reported previously, dietary supplementation with GABA significantly improved ADG (Hu et al, ; Wu, ; Xu, Zhang, Tang, & Tang, ) and F/G (Hu et al, ) in pigs but had no effect on ADFI (Hu et al, ; Li et al, ).We showed that the addition of 30 mg/kg GABA to the diet significantly improved ADG and F/G but did not significantly increase ADFI.…”
Section: Discussionmentioning
confidence: 99%
“…One such possibility is the known relationship between gut dysbiosis and greater inflammation (Sarkar, et al, 2016). Chronic inflammation has long been viewed as a contributor to cognitive decline (Trollor, et al, 2012) and there is some evidence that dysbiosis – rather than a specific phylum of bacteria – may lead to greater inflammation (Tilg & Kaser, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the present study found a cross-sectional relationship between the gut microbiome and cognitive test scores, but does not provide insight to possible mechanisms or trajectories of such a relationship. Prospective studies that include pre-/pro-biotic supplementation will shed light on the relationship between the gut microbiome and cognitive functioning, as they have been proposed as possible therapeutics for psychiatric conditions (Sarkar et al, 2016) and may provide similar benefits for neurological deficits. Additionally, antibiotics are known to affect the microbiome, and the 30 day exclusion criterion used here may not capture persons on longer or more frequent courses of antibiotics and may influence the observed findings.…”
Section: Discussionmentioning
confidence: 99%